Laboratory and Field Testing of Unsaturated Soils - Tarantino, Alessandro (Springer, 2017)
This collection focuses on recent advances in laboratory and field testing of unsaturated soils. Leading researchers from fourteen countries to represent global research in the area of experimental unsaturated soil mechanics have been invited to contribute to this book. Twelve reports are presented dealing with measurement and control of suction and water content, mechanical, hydraulic, and geo-environmental testing, microstructure investigation, and applications of unsaturated soil monitoring to engineering behaviour of geo-structures. The main motivation behind this book is the rapid growth of experimental unsaturated soil mechanics over the last couple of decades. Several innovative laboratory and field techniques have been introduced in mechanical, hydraulic, and geo-environmental testing. However, this information is widely dispersed in journals and conference proceedings and researchers and engineers beginning to work in the field of unsaturated soil mechanics may find it difficult to identify suitable equipment and instrumentation for research or professional purposes.